POSTMEMORIAL TRANSMISSION OF TRAUMA (Philological Studies, 2019)
Starting from Marianne Hirsch’s thesis that the notion of postmemory can be generalised in various contexts of traumatic transfer, this paper aims to elaborate on the interpretive validity of this concept in relation to the so-called Aegean Theme in Macedonian literature, that is, the theme of collective trauma caused by the exodus of Macedonian from Greece during the Greek Civil War (1944-1949). The subject of interest are the two works - Egejci and Snegot vo Kazablanka - by Macedonian authoress Kica Kolbe, member of the so-called post-generation. Considering that both books are of different genres—autobiography and novel—the analysis offers a comparative presentation of the narrative conventions taking part in the affirmation of their postmemorial dimension present in: the variant of postmemory, the elements of secondariness and of mediativeness of postmemory, as well as the postmemorial relation to the past through imagination, projection and creation.
Keywords: postmemory, memory, postgeneration, trauma, Aegean Theme